Law Enforcement Against Liquor Circulation - Umi Wahyu Nurhayati; Amin Purnawan; Ira Alia Maerani (Jurnal Daulat Hukum, 2019)
The problem in this research are: enforcement of the circulation of the liquor and the constraints of the enforcement of the circulation of liquor. Based on the results of the study concluded that: The police in law enforcement there are two (2) actions that persuasive action and repression which has its own purpose. In a persuasive action the police take preventive where often do counseling, provide guidance to the public about the dangers of alcohol. And invite various parties such as RT, RW, community leaders participated sertaandil in helping oversee the circulation of alcohol in their area. Constraints experienced as an investigator in conducting criminal investigations liquor circulation happens, is as follows: 1) Internal factors. In carrying out the investigation on the crime of liquor one such constraints is the current infrastructure of the police in tackling the crime of trafficking of liquor due to the lack of laboratory criminals who facilitate the investigation, because this place is useful as a means to prove with the naked eye between liquor original or fake. Lack of socialization conducted by the police. 2) external factors. This factor is of a society, of public awareness is relatively low which affects the smoothness in investigating criminal offenses circulation of alcohol, lack of awareness of the consequences of alcohol. Keywords: Law Enforcement; Circulation; Liquor.